Comparative Analysis of Superpanel Plates and Conventional Plates on the effect of Story Drift and Reinforcement of Column and Beam - Direja, Gusti Mulya; Baehaki, Baehaki; Soelarso, Soelarso (Jurnal Fondasi, 2024)
Building and non-building construction generally uses reinforced concrete using conventional methods. Over time, this method has evolved and given rise to other approaches such as precast and prestressed methods. However, these methods still have some drawbacks, such as the relatively high density of the material and its impact on other aspects of the structure. New innovations are emerging to solve these problems, such as super lightweight panels with a material density of around 650 kg/m3. This study aims to examine other structural components, namely beam and column structures by comparing the reinforcement requirements and deviation of two buildings with different types of floor plates. The tests were conducted using an analytical approach using ETABS software. The results showed that the average ratio of beam reinforcement between superpanel plate and conventional plate was 77% and column was 94%. The average ratio of X-direction deviation between superpanel plate and conventional plate is 94% and Y is 88%.